Sustainable alkali activated binders from a blend of biomass ash and iron sludge precursor - Darius Žūrinskas; Danutė Vaičiukynienė; Ruben Paul Borg; Laura Vitola (Scientific Reports)
Abstract Biomass ash is produced as a by-product of boiler combustion and most of this ash is disposed of in landfills. Biomass ash has a relatively low reactivity and alkali activated ash systems have poor mechanical properties. The inclusion of Fe-rich material in the precursor composition would increase the mechanical properties of alkali-activated binders. This study focuses on an alkali-activated binder made from blends of biomass fly ash from a power plant and iron sludge from a ship repair company. In the precursor blends, some of biomass fly ash were substituted by iron sludge, which consisted of high-volume Fe-rich compounds. After curing, the compressive strength was determined, and the strength values were explained by mineral composition and microstructure. Samples cured at higher temperature (at 60 °C for 24 h), iron sludge acted as a reactive component and reacted with NaOH to reduce its (NaOH) content in the system. For the samples cured at ambient temperature iron sludge acted as a less reactive component or like filler. Calcium aluminosilicate hydrate was not detected, but a higher amount of N-A/F-S-H and C-(A/F)-S-H gel formed compared to samples cured at higher temperature. Iron sludge incorporated into the matrix, making it more compact. These factors led to an increase in the strength values of the alkali-activated biomass fly ash incorporating the IS. The highest compressive strength of 9.8 MPa was achieved by samples cured at ambient temperature with 30% iron sludge. Thus, creating alkali activated binders is a promising way to use Fe-rich residues such as iron sludge from a ship repair company.